Loss of PPM1F expression predicts tumour recurrence and is negatively regulated by miR‐590‐3p in gastric cancer. (22nd February 2018) - Zhang, Jing; Jin, Ming; Chen, Xiaoyu; Zhang, Rui; Huang, Yanxia; Liu, Hui; Zhu, Jinshui
Abstract: Objectives: MicroRNAs (miRNAs) as small non‐coding RNA molecules act by negatively regulating their target genes. Recent studies have shown that protein phosphatase Mg2+/Mn2+‐dependent 1F (PPM1F) plays a critical role in cancer metastasis. But, the regulation mechanisms of PPM1F by miRNAs in gastric cancer (GC) remain undefined. Methods: The correlation of PPM1F or miR‐590‐3p (miR‐590) expression with clinicopathological features and prognosis of the patients with GC was analysed by TCGA RNA‐sequencing data. The miRNAs that target PPM1F gene were identified by bioinformatics and Spearman correlation analysis, and the binding site between miR‐590 and PPM1F 3′UTR was confirmed by dual luciferase assay. MTT and Transwell assays were conducted to evaluate the effects of miR‐590 or (and) PPM1F on cell proliferation and invasion. Results: We found that PPM1F expression was downregulated in GC tissues and cell lines and was correlated with tumour recurrence in patients with GC. The decreased expression of PPM1F was attributed to the dysregulation of miR‐590 expression rather than its genetic or epigenetic alterations. Overexpression of miR‐590 promoted cell proliferation and invasion capability of GC cells, while knockdown of miR‐590 reversed these effects. Moreover, PPM1F was validated as a direct target of miR‐590 and counteracted the tumour‐promoting effects caused by miR‐590. The expression of miR‐590 presented the negative correlation with PPM1F expression and acted as an independent prognostic factor for tumour recurrence in patients with GC. Conclusion: PPM1F may function as a suppressive factor and is negatively regulated by miR‐590 in GC.